Dakwah Ustadzah Halimah Alaydrus Mengenai Akhlak Baik Kunci Keberhasilan Dunia Akhirat: Analisis Pentingnya Akhlak Pada Generasi-Z - Samsul Rifa’i (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This article presents a study of the da'wah of ustadzah Halimah Alydrus regarding Good Morals as the key to Success in the Hereafter. Someone has good morals is very necessary, because it is one of the keys to success in the afterlife. Good morals will bring ourselves to be good too, and the surrounding environment will support the good things we do. Having good morals does not only apply to children, but also to parents, wives, husbands, mothers, and others must have good morals. Good manners are the manners of the Prophet Muhammad SAW, because his morals is the Qur'an which is certainly good and noble. So we must imitate the morals of the Prophet Muhammad SAW. This article also discusses a brief bio of who Ustadzah Halimah Alaydrus is, and why we raised this topic as our report. We also see the fact in the field that many teenagers whose morals have declined, and some are far from good morals, it can affect the future of the nation in the future.